Regional Autonomy System: Delegation of Authority and Power of Regional Government in Indonesia in the Study of Fiqh Siyasah - Mukhlis, Muhammad Mutawalli; Maskun, Maskun; Tajuddin, Muhammad Saleh; Aslan, Jamal; Hariyanto, Hariyanto; Samosir, Hotlan (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This research aims to find out the implementation of regional autonomy in Indonesia in general and also to find out about Fiqh Siyasah's view on the implementation of regional autonomy in Indonesia. A qualitative approach was used in conducting this research and data was obtained through relevant literature studies. The result, Islam provides space for ijtihad in the area of ​​siyasah or state politics provided that it is done to achieve the goals of benefit and justice as well as the welfare of the general public. One of the things related to the siyasah area is related to the implementation of regional autonomy in Indonesia. Basically, the provision of regional autonomy in Indonesia is a space to provide opportunities for each region in this country to explore and develop the potential of each region in order to provide prosperity for regional communities. The conclusion, this article highlights the importance of local government autonomy within a federal structure to encourage grassroots democracy and self-governance. Islamic law does not have specific rules regarding regional autonomy, and this concept emerged during the reform era to promote justice and prosperity. However, Islam still acknowledges the concept of baldatun thayyibatun, which is based on the Qur'an and the Sunnah of the Prophet.